Identifying the Factors Causing Delay of Shop Drawings Process ‎in Construction Projects: A Case Study (Journal of University of Babylon for Engineering Sciences, 2025)
Adhering to the project timeline without delays is a major challenge that demonstrates the efficiency of construction projects. Delays can be controlled if their real causes have been evaluated properly. Delay in submitting/ approving engineering shop drawings is more often encountered in projects. Therefore, it is important to investigate the reasons of the shop drawings delay. This study aims to identify and evaluate the factors causing delays in the process of implementing engineering shop drawings in the Iraqi construction market. To achieve this aim, a comprehensive review of previous literatures was conducted to identify the reasons of project delays, analyze its findings, and highlight its relevance to this study. Based on the literature review findings, twenty specific causes of work delays related to project schedule, cost, and stakeholder performance were identified and investigated through a structured survey conducted by 49 Iraqi engineers. This research is quantitative relies on the statistical approach to analyze the data. The results were presented and analyzed using a Pareto chart. The calculations were performed sequentially as follows: calculating the importance index (IMP.I) for each item, sorting them in descending order to obtain the cumulative frequency percentage, and then importing the results into a Pareto chart. Based on the chart's output, the 20 factors have the same degree of influence on the preparation of working shop drawings and should receive the same degree of attention while trying to minimize their impact on project performance. Therefore, the project team will need to overcome the impact of the first 10 causes to solve 52% of the delay problem, the first 15 factors to solve the 77%, and so on until 100% is solved. The findings from this study can be used to develop strategic plans for preventing and eliminating delay factors. However, the project's budget and site conditions primarily determine the priority of these methods and techniques.